Students’ Conceptions of Challenges in Writing Thesis: A Case of Postgraduate Context - Mohamad Yunus; Bachtiar Bachtiar; Syafruddin Syafruddin; Juhana Juhana; Dewi Maharani Rachmaningsih (STAI Hubbulwathan Duri, 2023)
The ability to apply correct and appropriate academic writing becomes a crucial requirement in composing scientific papers. Many researchers suggested that the intensity of reading and writing habits have a significant impact and determines students’ ability to put ideas in writing. This study aimed to identify the main challenges faced by postgraduate students of Universitas Terbuka in writing and finalizing their thesis, including difficulties in creating good and correct written Indonesian language. This research employed mixed method research (MMR) with three research instruments for data collection, namely questionnaires, semi-structured interviews, and document analysis. There were 165 students participated in answering the questionnaire, and 24 students and 16 lecturers from 7 study programs were involved in the interviews. Thirty proposals for master’s thesis were analyzed by using a document analysis method. The research participants were purposefully selected using purposive sampling. The research findings showed that the aspects that were considered the easiest in writing the thesis are the literature review section and the conclusions and suggestions section. While the most difficult parts of the thesis were the introduction and discussion sections. The research also found that students were still very constrained in terms of good and correct written Indonesian language skills.